Christian Leadership Paradigm According to Thomas Aquinas and Social Transformation: A Theological Study and Case Analysis - Budi Tjahja Halim (Eduvest - Journal of Universal Studies, 2026)
This study explores the Christian leadership paradigm based on the 13th-century philosophy of Thomas Aquinas, focusing on its relevance to contemporary leadership practices, especially in addressing social transformation. Amid growing challenges such as moral crises and social inequality, the need for ethical, spiritually grounded leadership has become urgent. The purpose of this study is to examine how Thomistic principles caritas (charity), prudentia (wisdom), justitia (justice), and bonum commune (common good) can guide modern Christian leadership. Using a qualitative descriptive methodology, this research conducted a theological hermeneutic analysis of Aquinas's writings, comparing them with real-world social transformation examples, such as the La Red community's impact on Bellavista Prison. The results reveal that Thomistic leadership principles provide a moral and ethical framework that not only fosters organizational effectiveness but also drives social change. By focusing on service, justice, and moral integrity, the study highlights how these principles can address the pressing issues of public integrity, structural poverty, and social solidarity in today's context. The conclusion suggests that the Thomistic model of leadership is not merely a theoretical construct but a practical tool for transforming societal structures through moral virtue and a commitment to the common good. Future research could expand on these findings in diverse organizational contexts.